Effects of resistance training on running economy and cross-country performance - Barnes, K. R.; Hopkins, W. G.; McGuigan, M. R.; Northuis, M. E.; Kilding, A. E. (Medicine & Science in Sports & Exercise, 2013)
Purpose: Heavy-resistance training and plyometric training offer distinct physiological and neuromuscular adaptations that could enhance running economy and, consequently, distance-running performance. To date, no studies have examined the effect of combining the two modes of training on running economy or performance.